PERBEDAAN HASIL UJIAN NASIONAL PADA TINGKAT SATUAN PENDIDIKAN SEKOLAH MENENGAH ATAS DI KABUPATEN TOBA SAMOSIR BERDASARKAN AKREDITASI (Studi Kasus di Kabupaten Toba Samosir) - Sinta Dameria Simanjuntak (MES: Journal of Mathematics Education and Science, 2017)
Abstract. This study is a quasi-experimental study. The objectives of this research are: (1) to analyze the difference of the result of the National Examination of Mathematics of the students based on the accreditation of the school, (2) to analyze the difference of the result of the National Exam Combined students based on the school accreditation, and (3) to analyze the difference of National Examination result based on the students ability. The results of this study indicate that there is no difference in the value of the National Examination of Mathematics based on accreditation. Where in this study, better accreditation does not guarantee better result of Mathematics National Exam result. On the contrary, in this study found the results of research that schools with lower accreditation have a better result of the National Examination of Mathematics. There is no difference in the value of the result of the Joint National Exam based on accreditation. Where in this study, better accreditation does not guarantee better results of the Joint National Examination results. On the contrary, in this study found the results of research that schools with lower accreditation have a better result of the Joint National Exam results. There is no difference in the results of the Joint National Exam based on the accreditation and the level of students' Mathematics abilities. Where school accreditation and Mathematics ability level does not cause significant difference in National Examination results. Keywords: National Exam and Accreditation.  Abstrak. Penelitian ini adalah penelitian kuasi eksperimen. Tujuan penelitian ini adalah: (1) menganalisis perbedaan hasil Ujian Nasional Matematika siswa berdasarkan akreditasi sekolah, (2) Menganalisis perbedaan hasil Ujian Nasional Gabungan siswa berdasarkan akreditasi sekolah, dan (3) menganalisis perbedaan hasil Ujian Nasional berdasarkan kemampuan siswa. Hasil penelitian ini menunjukkan bahwa tidak terdapat perbedaan nilai hasil Ujian Nasional Matematika berdasarkan akreditasi. Dimana dalam penelitian ini, akreditasi yang lebih baik tidak menjamin nilai hasil Ujian Nasional Matematika yang lebih baik. Malah sebaliknya, dalam penelitian ini ditemukan hasil penelitian bahwa sekolah dengan akreditasi yang lebih rendah memiliki nilai hasil Ujian Nasional Matematika yang lebih baik. Tidak terdapat perbedaan nilai hasil Ujian Nasional Gabungan berdasarkan akreditasi. Dimana dalam penelitian ini, akreditasi yang lebih baik tidak menjamin nilai hasil Ujian Nasional Gabungan yang lebih baik. Malah sebaliknya, dalam penelitian ini ditemukan hasil penelitian bahwa sekolah dengan akreditasi yang lebih rendah memiliki nilai hasil Ujian Nasional Gabungan yang lebih baik. Tidak terdapat perbedaan hasil Ujian Nasional Gabungan berdasarkan akreditasi dan tingkat kemampuan Matematika siswa. Dimana akreditasi sekolah dan tingkat kemampuan Matematika tidak menyebabkan perbedaan hasil Ujian Nasional yang signifikan. Kata Kunci: Ujian Nasional dan Akreditasi